Leukotriene B4 receptor locus gene characterisation and association studies in asthma - Tulah, Asif S.; Beghé, Bianca; Barton, Sheila J.; Holloway, John W.; Sayers, Ian (BioMed Central, 2012)
Background: Polymorphisms spanning genes involved in the production of leukotriene B4 (LTB4) e.g. ALOX5AP and LTA4H are associated with asthma susceptibility, suggesting a role for LTB4 in disease. The contribution of LTB4 receptor polymorphism is currently unknown. The aim of this study was to characterise the genes for the two pivotal LTB4 receptors, LTB4R1 and LTB4R2 in lung tissue and determine if polymorphisms spanning these genes are associated with asthma and disease severity. Methods: Rapid amplification of cDNA ends (RACE) was used to characterise the LTB4R1 and LTB4R2 gene structure in lung. The LTB4R1/2 locus on chromosome 14q11.2 was screened for polymorphic variation. Six LTB4R single nucleotide polymorphisms (SNPs) were genotyped in 370 Caucasian asthma families and 299 Adult Asthma Individuals (n=1877 total) and were evaluated for association with asthma and severity (BTS) outcome measures using Family Based Association Test, linear regression and chi square. Results: LTB4R1 has complex mRNA arrangement including multiple 50 -untranslated exons, suggesting additional levels of regulation. Three potential promoter regions across the LTB4R1/2 locus were identified with some airway cell specificity. 22 SNPs (MAF>0.01) were validated across the LTB4R locus in the Caucasian population. LTB4R1 and LTB4R2 SNPs were not associated with asthma susceptibility, FEV1 or severity. Conclusions: LTB4R1 and LTB4R2 shows splice variation in the 50 -untranslated region and multiple promoter regions. The functional significance of this is yet to be determined. Both receptor genes were shown to be polymorphic. LTB4R polymorphisms do not appear to be susceptibility markers for the development of asthma in Caucasian subjects